Dual driving forces for corporate environmental responsibility performance: The synergistic effects of government environmental regulation and market multi-agent green supervision - Zhao, Jingsong; Zhang, Chen; Wu, Yong; Zhu, Jing (The Science of the total environment, 2024)
The 26th United Nations Climate Change Conference reached a series of agreements on implementing the Paris Agreement, empowering governments to independently establish emission reduction goals and encouraging market participants to invest in sustainable development. It highlighted that enhancing corporate environmental responsibility performance (CERP), driven by the collaborative efforts of government and market forces, is key to achieving global sustainability. In this context, this study is the first attempt to investigate the synergistic effects of government environmental regulation (GER) and market multi-agent green supervision (MGS) on CERP. The findings are as follows. First, GER, encompassing the multidimensional environmental responsibilities of governments, has not effectively spurred CERP. MGS, incorporating the green concerns of diverse investors and intermediaries, serves as a significant catalyst for enhancing CERP. The synergy between GER and MGS, involving multi-stakeholder collaborative governance, plays a significant motivating role in promoting CERP. Second, financing constraints and executives' attention to corporate environmental responsibility (CER) are two key channels through which the synergy between GER and MGS influences CERP. Third, firms located in regions with better economic development, those operating in non-heavily polluting industries, or non-state-owned firms exhibit heightened proactivity in improving CERP under the synergy between GER and MGS. This paper expands research on multi-agent collaborative environmental governance from the regional macro-perspective to the micro-firm level, providing a fresh perspective and theoretical basis. The novel findings offer valuable insights for policymakers and firms, especially in economies similar to China, in containing growing environmental challenges and advancing global sustainability. [Display omitted] •Designed a novel theoretical framework of collaborative governance of GER and MGS.•Developed a multi-subject synergy-based measure to quantify the degree of synergy between GER and MGS.•The synergy between GER and MGS serves as a significant catalyst for enhancing CERP.•Financing constraints and executives’ attention to CER play mediating roles in the mechanism.•The synergistic effects of GER and MGS on CERP are heterogeneous among different types of firms.